Pengaruh Bola Gantung terhadap Kecepatan Tendangan Sabit Pencak Silat pada Usia Remaja - Kusuma, Esa Aryani; Muhtar, Tatang; Sudirjo, Encep (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The purpose of this study was to examine the influence of hanging ball training on the speed of crescent kicks in Pencak Silat among adolescents. The research used a quantitative experimental method with a pre-experimental one-group pretest-posttest design. The population included all members of the Tadjimalela Pencak Silat School in Soreang, with a sample of 16 adolescents aged 12-15 years selected through purposive sampling. Data analysis involved homogeneity, normality, and paired t-tests using SPSS. Results indicated a significant increase in the speed of crescent kicks after hanging ball training, with mean pretest scores of 16.56 for left kicks and 17.88 for right kicks, and posttest scores of 18.44 and 20.06, respectively. The paired t-test showed significant improvements (p < 0.05) in kick speed for both legs. Conclusion, that hanging ball training effectively enhances the speed of crescent kicks in Pencak Silat. Keywords: hanging ball, speed, sickle signature